SYSTEMIC INFLAMMATORY RESPONSE AFTER TRANSRECTAL VS TRANSPERINEAL PROSTATE BIOPSY - Husain, Gladwyn Ayudia; Seputra, Kurnia Penta; Budaya, Taufiq Nur (Indonesian Urological Association, 2026)
Objective: This study compares the inflammatory responses of TR and TP biopsies, using the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) as biomarkers. Material & Methods: A retrospective cohort study was conducted at Dr. Saiful Anwar General Hospital, Malang, Indonesia, from January 2023 to August 2025, involving 46 patients who underwent TR or TP biopsies. Pre- and post-procedure blood samples were analyzed for NLR and PLR. Statistical analysis was performed using SPSS, employing paired t-tests and Mann-Whitney U tests. Results: NLR before the procedure was significantly higher in the TR group (p = 0.034). Post-procedure, there were no significant changes in NLR or PLR (p > 0.05). Infections and fever occurred more frequently in the TR group (12% and 24%, respectively), with no complications in the TP group. Prostate cancer detection rates were similar between both groups (p = 0.760). Discussion: Both biopsy methods induced systemic inflammation, as reflected by increased NLR and PLR post-procedure. However, TR biopsies were linked to a higher incidence of infections and febrile episodes. This aligns with prior studies indicating a greater complication rate with TR biopsies. NLR may serve as a potential biomarker for assessing tumor aggressiveness, especially in TR biopsy patients, where NLR changes were more pronounced among those diagnosed with prostate cancer. Conclusion: TP biopsies present lower infection risk and similar diagnostic accuracy compared to TR biopsies. NLR and PLR may be useful biomarkers for tracking inflammatory responses post-biopsy. Larger studies are needed to confirm these findings. Keywords: Prostate cancer, prostate biopsy, transrectal biopsy, transperineal biopsy, NLR, PLR, inflammatory response, infection.